2020
DOI: 10.1136/bmjopen-2020-042424
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in avoidable hospitalisation in large urban areas: retrospective observational study in the metropolitan area of Milan

Abstract: ObjectiveSignificant inequalities in access to healthcare system exist between residents of world megacities, even if they have different healthcare systems. The aim of this study was to estimate avoidable hospitalisations in the metropolitan area of Milan (Italy) and explore inequalities in access to healthcare between patients and across their areas of residence.DesignRetrospective observational study.SettingPublic and accredited private hospitals in the metropolitan area of Milan. Data obtained from the hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
(30 reference statements)
0
6
0
Order By: Relevance
“… 15 , 16 , 17 Regression results here for age, sex and educational level effects on total AH ( Table 2 ) echo results recently observed using the HDR to measure AH for the metropolitan area of Milan, a study that also found declining rates of hospitalizations and age-adjusted and overall rates of AH over time (2005-2016). 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 , 16 , 17 Regression results here for age, sex and educational level effects on total AH ( Table 2 ) echo results recently observed using the HDR to measure AH for the metropolitan area of Milan, a study that also found declining rates of hospitalizations and age-adjusted and overall rates of AH over time (2005-2016). 12 …”
Section: Discussionmentioning
confidence: 99%
“…AHs are hospitalizations due to ambulatory care sensitive conditions (ACSC), i.e., medical conditions for which hospitalization is not needed when primary care is timely and effective. 9 The incidence of AHs and ACSCs has been extensively used to proxy for quality of, and access to, preventive health services within and across countries 9 , 10 , 11 , 12 and to detect inequalities related to race and ethnicity, 13 , 14 socioeconomic conditions, 15 , 16 , 17 and immigrant status. 13 , 18 , 19 In the European context, evidence on immigrants’ AH rates is relatively recent 18 and in general shows that immigrants experience a higher risk of AHs, although results differ by country, reason to migrate and illness.…”
Section: Introductionmentioning
confidence: 99%
“…Lombardy is the most populated region in Italy, counting one-sixth of the Italian population, and according to the Italian National Institute of Statistics (22), it ranked first for the total number of non-Italian citizens. Milan, its administrative centre, has a population of approximately 1.4 million inhabitants, including over 200,000 foreigners, mainly in the suburbs (23). Children aged 2-6 years old are about 55,000, of which 27% do not have the Italian citizenship.…”
Section: Contextmentioning
confidence: 99%
“…Avoidable hospitalizations are those that can be avoided through timely, effective, and adequate primary health care services (6). If patients have access to timely and effective ambulatory care, it is possible to reduce hospitalizations for these conditions by preventing the occurrence of diseases or managing chronic conditions in an outpatient setting (7). Diabetes mellitus has now been included in many index systems of avoidable hospitalizations diseases across the world (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%